Tanggung Jawab Pemerintah Dalam Melakukan Pengawasan Sertifikasi Label Halal Di Derah - Harjuna, Dian Adinda; Lekipiouw, Sherlock Halmes; Pattinasarany, Yohanes (Faculty of Law Universitas Pattimura, 2025)
Indonesia as a country with a majority Muslim population has a high need for halal products. Halal certification and labeling not only serve as a religious guarantee, but also as a form of legal protection for consumers in ensuring the safety and authenticity of products. This study aims to analyze the form of responsibility of the government, both central and regional, in supervising halal label certification and the legal consequences if these responsibilities are not carried out. This research uses a normative juridical method with a legislative approach, a conceptual approach and uses primary and secondary legal materials. The results of the study show that the government has supervisory responsibilities in two forms: preventive supervision carried out before the product is circulated and repressive supervision after the product is circulated. This supervision is carried out by BPJPH in collaboration with LPH, MUI, and local governments. If supervision is not carried out, there is a potential for the circulation of non-halal products that have been labeled halal, causing public unrest and violations of the law. The government may be subject to administrative and criminal sanctions based on applicable regulations. Therefore, sustainable, transparent, and accountable supervision is needed to ensure the halalness of products and the protection of the rights of Muslim consumers, as well as as the implementation of the principles of good governance.